Non-innocence and mixed valency in tri- and tetranuclear ruthenium complexes of a heteroquinone bridging ligand. Issue 44 (2nd November 2017) - Ansari, Mohd. Asif; Mandal, Abhishek; Beyer, Katharina; Paretzki, Alexa; Schwederski, Brigitte; Kaim, Wolfgang; Lahiri, Goutam Kumar
Abstract : The potential of a heteroquinone to bridge up to four metal fragments has been structurally elucidated and multiple redox processes have been ascertained. Abstract : The redox-active ligand 5, 7, 12, 14-tetraazapentacene-6, 13-quinone = L forms structurally characterised compounds with three (1 ) or four (2 ) [Ru(acac)2 ] complex fragments in which each of the metals is N, O-chelated. The new tris- and tetrakis-bidentate chelate compounds exhibit ruthenium centres bridged at about 4 Å by quinone O atoms which are then situated across the pentacene π system at about 6–8 Å distance. Several electron transfer processes were observed by voltammetry (CV, DPV) and the intermediates identified by EPR and UV-Vis-NIR spectroelectrochemistry. TD-DFT calculations were applied to assign the proper oxidation states within the multistep redox systems {(μ n -L)[Ru(acac)2 ] n } k, n = 3 or 4, revealing both metal and ligand based electron transfer.